Kakas Bantu Penilaian Kopling Menggunakan Metrik Indirect Package Coupling Based on Responsibilty - Muhammad Ridha Anshari; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Rapid development in technology has significantly increased the needs of software maintenance to keep it relevant. The better the quality of the software's design, the easier it is to maintain. That quality can be measured using coupling metric. Indirect dependency between modules needs to be considered for better computational accuracy, which indirect package coupling based on responsibility metric provides. In order to tackle these problems, the package coupling evaluation tool using the indirect package coupling based on responsibility metric is built. The input data is a package diagram file that is exported into an XML (eXtensible Markup Language) format, which can be achieved using a software like Visual Paradigm. The system will parse the file using DOM (Document Object Model) parser. The tool was tested through unit and integration testing using white box testing technique, and validation testing using black box testing technique. It's performance is tested using packages from JDraw's 3 simplified package diagram, which are event, gui, and action. The result shows that this tool can save about 10 minutes and 27.1188 seconds of time needed by human in evaluating the event package's coupling.